Frequency of hypertriglyceridemic waist phenotype and its association with metabolic abnormalities in adolescents from a Andean region of Peru - García-Flores, Segunda Aydeé (2022)
Introduction. The hypertriglyceridemic waist has been proposed as a phenotype with a strong association with the metabolic syndrome. The frequency of this phenotype in adolescents from Peru, including Andes population is unknown. Objective. To estimate the frequency of the hypertriglyceridemic waist and its association with metabolic abnormalities and other factors in Peruvian adolescents from an Andean region. Methods. We performed a data secondary analysis through cross-sectional design. We analyzed 397 randomly selected adolescents from two public schools in the Cajamarca city. We defined hypertriglyceridemic waist as the simultaneous presence of increased waist circumference (≥ 90th percentile for age and sex) and serum hypertriglyceridemia (≥110 mg/dL). We estimated the point prevalence of hypertriglyceridemic waist and their 95% confidence interval, we also performed a binary logistic regression analysis to identify associated risks. Results. The phenotype of hypertriglyceridemic waist was 2.01% (95%CI: 0.51 to 3.52). The most frequent component was hypertriglyceridemia with 39.55% (95%CI: 34.61 to 44.48), while increased waist circumference affected 3.02% (95%CI: 1.21 to 4.83). Excess weight was the only variable association with hypertriglyceridemic waist phenotype (adjusted OR: 62.7; 95%CI: 6.7 - 587.9; p<0.001). Conclusions. Two of one hundred adolescents aged 11 to 17 years living in a high Andean region of Peru had the hypertriglyceridemic waist phenotype. This phenotype was associated with excess weight.